Regulatory Framework for Advanced Therapy Medicinal Products in Europe and United States - Iglesias-Lopez, Carolina; Agustí, Antonia; Obach, Mercè; Vallano, Antonio (Frontiers in Pharmacology, 2019)
Advanced therapy medicinal products (ATMPs) are a fast-growing field of innovative therapies. The European Union (EU) and the United States (US) are fostering their development. For both regions, ATMPs fall under the regulatory framework of biological products, which determines the legal basis for their development. Sub-classifications of advanced therapies are different between regions; while in EU there are four major groups, i.e. gene therapy, somatic cell therapy, tissue engineered therapies and combined advanced therapies, in US the sub-classification covers two major groups of products, i.e. gene therapy and cellular therapy. The inclusion criteria that define a gene therapy are equivalent in both regions, and the exclusion criteria are directly related to the indications of the product. In the EU, there is a clear differentiation between cell and tissue-based products regarding their classification as advanced therapies or coverage by other legal frameworks, whereas in US there is a broader classification about whether or not these products can be categorized as biologic products. Both in EU and in US, in order to classify a cell or a tissue-based product as an advanced therapy, it must be ensured that the processing of the cells implies a manipulation that alters their biological characteristics, although the term of manipulation in US differentiates between structural and non-structural cells and tissues. The regulatory terminology used to define ATMPs and their sub-classification reveals some differences between EU and US.